A Call to Rethink Nursing Education in Zimbabwe. (January 2022) - Chigangaidze, Kudzanayi A. N.
Nursing education is crucial in the achievement of The United Nations 2015 Sustainable Development Goal 3 that aims to "ensure healthy lives and promote wellbeing for all ages". Zimbabwe produces diploma and degree graduates from the available education programs in the country. The differences in the diploma and degree education program include the curricula, program funding, quality assurance processes, personnel delivering the programs, student exchange programs and partnerships. Graduates from both programs are not required to have licensure examinations to test their competency before practising. The diploma program has failed to produce graduates who are critical thinkers due to the shallow nature of the learning curriculum. Additionally, the graduates are not involved in strategic decision making in the profession. In the interest of quality and patient safety, it would be appropriate to phase out the diploma program and adopt the baccalaureate nursing degree.